EXECUTING GOOGLE CLASSROOM IN TEACHING READING COMPREHENSION DURING PANDEMIC - Rachmanita; Kiki Rizki Amelia; Dita Septiana Kharisma Putri (Universitas Islam Ogan Komering Ilir Kayuagung, 2022)
The study's primary aim was to discover whether there was a significant difference in reading ability between students who were taught using Google Classroom and those who were not. In this investigation, a quasi-experimental method was used. This study's representative sample was 82 students, split into two groups experimental (VIII 2) and control (VIII 5), each of which had 41 students. To capture and analyze data, a written test of reading ability in the form of multiplechoice questions was performed. The data was analyzed using the T-test. The independent t-test showed a significant level of p0.05 with df 80, and the critical value of t-table = 1.990. Because the obtained t-value (3.179) was greater than the critical value t-table (1.990), Ho was rejected and Ha accepted. It intended that there was a significant difference in reading ability between students taught using Google Classroom and those who were not